2006
DOI: 10.1038/modpathol.3800627
|View full text |Cite
|
Sign up to set email alerts
|

Expression and possible role of hPTTG1/securin in cutaneous malignant melanoma

Abstract: Human pituitary tumour-transforming gene 1 or hPTTG1 is a proto-oncogene that codes for securin, a protein involved in sister chromatid separation. Based on previous microarray data, we studied the expression of hPTTG1/securin in melanocytic lesions. In contrast to nevi and radial growth phase melanomas, securin was expressed by scattered cells in the vertical growth phase, suggesting a role in tumour progression. In a series of 29 nodular and 29 superficial spreading melanomas, matched for all histological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…We show for the first time that the effect of CDC23 knockdown on cellular proliferation could be reversed by the simultaneous knockdown of cyclin B1 and securin. This finding suggests that the effect of CDC23 is mediated, at least in part, by cyclin B1 and securin which is consistent with the role of these two proteins in cancer progression (Bowers & Boylan 2004, Borlak et al 2005, Winnepenninckx et al 2006, Salehi et al 2008.…”
Section: Discussionsupporting
confidence: 70%
“…We show for the first time that the effect of CDC23 knockdown on cellular proliferation could be reversed by the simultaneous knockdown of cyclin B1 and securin. This finding suggests that the effect of CDC23 is mediated, at least in part, by cyclin B1 and securin which is consistent with the role of these two proteins in cancer progression (Bowers & Boylan 2004, Borlak et al 2005, Winnepenninckx et al 2006, Salehi et al 2008.…”
Section: Discussionsupporting
confidence: 70%
“…However, the respective roles of the biological characteristics of micrometastatic tumor cells and SLN immune response remain largely unknown. In a genomics study of primary melanomas, we found that primary melanomas with metastatic evolution were characterized by a dysregulation in key pathways driving replication, including the replication origins firing (ROF) system and survivin gene involved in chromatid separations (37,38). We found no difference in expression signature between primary melanomas and metastases, illustrating once more that the genetic machinery for melanoma metastases evolution is acquired early in melanoma development.…”
Section: Discussionmentioning
confidence: 78%
“…In colorectal cancers patients, such instability correlates with higher tumor grade, indicating that PTTG and genetic instability may be linked in these tumors (Kim et al 2007a). PTTG expression also correlates with aneuploidy in melanomas (Winnepenninckx et al 2006) and in follicular as well as papillary thyroid carcinomas . In vitro transfection of colorectal (Kim et al 2007a) and follicular thyroid as well as of HeLa and A549 cells (Mu et al 2003) has been shown to induce both genetic instability and aneuploidy.…”
Section: Genetic Instabilitymentioning
confidence: 93%
“…In a series of 29 nodular and 29 superficial spreading melanomas, PTTG correlated with aneuploidy as well as the nodular type (Winnepenninckx et al 2006). The expression of PTTG mRNA in multiple myeloma (NZ33) has been shown to be significantly higher than in normal controls .…”
Section: Uterusmentioning
confidence: 99%
See 1 more Smart Citation